Extracorporeal photopheresis induces the release of anti-inflammatory fatty acids and oxylipins and suppresses pro-inflammatory sphingosine-1-phosphate - Gerhard Hagn; Ara Cho; Nina Zila; Barbara Sterniczky; Christian Jantschitsch; Dexin Dong; Andrea Bileck; Mariia Koren; Philipp Paulitschke; Thomas Mohr; Robert Knobler; Wolfgang Peter Weninger; et al. (Inflammation Research, 2025)
Aims Extracorporeal photopheresis (ECP) is a UVA-based phototherapy of whole blood and well established as a first line or combination therapy for the treatment of cutaneous T-cell lymphoma, systemic sclerosis, graft-versus-host disease and is used to control organ transplant rejection. While the proapoptotic activity on activated T-cells is evident, the clinical efficacy of this treatment also appears to be based on other yet unknown mechanisms. In this study, we aimed to identify novel mechanisms of ECP regardless of the patient’s background situation. Main methods To better understand the immediate consequences of ECP, we analyzed blood plasma of patients with different ECP indications immediately before and after treatment with regard to proteins and lipid mediators. Key findings While proteome profiling identified substantial inter-individual differences in the protein composition, no significant alteration was detectable upon treatment. In contrast, several fatty acids and lipid mediators were found to be significantly altered by ECP. Remarkably, upregulated lipid mediators including polyunsaturated fatty acids, 12-HEPE and 13-OxoODE have been described to be anti-inflammatory, while the downregulated molecules sphingosine-1-phosphate (S1P) and stearic acid are potent pro-inflammatory mediators. A selective sphingosine-1-phosphate-1 receptor (S1P1) modulator AUY954, which decreases S1P1 and experimentally reduces transplant rejection in vivo, showed greater anti-proliferative activity in human lung fibroblasts from COPD patients compared to normal lung fibroblasts, confirming that this pathway may be important in ECP and its mode of action. Significance and outlook In conclusion, we suggest that the ECP-induced changes in lipid mediators may contribute to the remarkable anti-inflammatory effects of the treatment. Depending on their lipid status, patients may benefit from novel treatment regimens combining ECP with lipid modulators. This could be used for the prevention of transplant organ rejection, the treatment of acute or chronic GvHD or transplant organ rejection and the long-term treatment of various skin diseases. This study uncovers novel mechanisms of ECP, that can be used to establish clinically relevant lipid profiles of patients to support patient stratification, predictive or prognostic purposes and thus personalized medical care in the framework of PPPM practice. A combination with S1P modulators may therefore have beneficial effects.

Mass spectrometry-based analysis of eccrine sweat supports predictive, preventive and personalised medicine in a cohort of breast cancer patients in Austria - Michael Bolliger; Daniel Wasinger; Julia Brunmair; Gerhard Hagn; Michael Wolf; Karin Preindl; Birgit Reiter; Andrea Bileck; Christopher Gerner; Florian Fitzal; Samuel M. Meier-Menches (EPMA Journal, 2025)
Objective Metabolomics measurements of eccrine sweat may provide novel and relevant biomedical information to support predictive, preventive and personalised medicine (3PM). However, only limited data is available regarding metabolic alterations accompanying chemotherapy of breast cancer patients related to residual cancer burden (RCB) or therapy response. Here, we have applied Metabo-Tip, a non-invasive metabolomics assay based on the analysis of eccrine sweat from the fingertips, to investigate the feasibility of such an approach, especially with respect to drug monitoring, assessing lifestyle parameters and stratification of breast cancer patients. Methods Eccrine sweat samples were collected from breast cancer patients ( n = 9) during the first cycle of neoadjuvant chemotherapy at four time points in this proof-of-concept study at a Tertiary University Hospital. Metabolites in eccrine sweat were analysed using mass spectrometry. Blood plasma samples from the same timepoints were also collected and analysed using a validated targeted metabolomics kit, in addition to proteomics and fatty acids/oxylipin analysis. Results A total of 247 exogenous small molecules and endogenous metabolites were identified in eccrine sweat of the breast cancer patients. Cyclophosphamide and ondansetron were successfully detected and monitored in eccrine sweat of individual patients and accurately reflected the administration schedule. The non-essential amino acids asparagine, serine and proline, as well as ornithine were significantly regulated in eccrine sweat and blood plasma over the therapy cycle. However, their distinct time-dependent profiles indicated compartment-specific distributions. Indeed, the metabolite composition of eccrine sweat seems to largely resemble the composition of the interstitial fluid. Plasma proteins and fatty acids/oxylipins were not affected by the first treatment cycle. Individual smoking habit was revealed by the simultaneous detection of nicotine and its primary metabolite cotinine in eccrine sweat. Stratification according to RCB revealed pronounced differences in the metabolic composition of eccrine sweat in these patients at baseline, e.g., essential amino acids, possibly due to the systemic contribution of breast cancer and its impact on metabolic turnover. Conclusion Mass spectrometry-based analysis of metabolites from eccrine sweat of breast cancer patients successfully qualified lifestyle parameters for risk assessment and allowed us to monitor drug treatment and systemic response to therapy. Moreover, eccrine sweat revealed a potentially predictive metabolic pattern stratifying patients by the extent of the metabolic activity of breast cancer tissue at baseline. Eccrine sweat is derived from the otherwise hardly accessible interstitial fluid and, thus, opens up a new dimension for biomonitoring of breast cancer in secondary and tertiary care. The simple sample collection without the need for trained personnel could also enable decentralised long-term biomonitoring to assess stable disease or disease progression. Eccrine sweat analysis may indeed significantly advance 3PM for the benefit of breast cancer patients.

Exposure to dietary fatty acids oleic and palmitic acid alters structure and mechanotransduction of intestinal cells in vitro - Janice Bergen; Martina Karasova; Andrea Bileck; Marc Pignitter; Doris Marko; Christopher Gerner; Giorgia Del Favero (Archives of Toxicology, 2023)
Intestinal cells are continuously exposed to food constituents while adapting to peristaltic movement and fluid shear stress. Oleic acid (OA) and palmitic acid (PA) are among the most prevalent fatty acids with respect to dietary lipids. Despite the central importance of dietary lipids for a balanced diet, awareness about potential detrimental effects related to excessive consumption is increasing; this includes toxicity, metabolic deregulation, and, particularly for cancer cells, a benefit from the uptake of fatty acids related to promotion of metastasis. Expanding on this, we started elucidating the effects of OA and PA (25–500 µM) on non-transformed human intestinal epithelial cells (HCEC-1CT) in comparison to colon carcinoma cells (HCT116), with regard to the mechanosensory apparatus. Hence, intestinal cells’ motility is on the one side essential to ensure adaption to peristaltic movement and barrier function, but also to enable metastatic progression. Incubation with both OA and PA (≥ 25 µM) significantly decreased membrane fluidity of HCT116 cells, whereas the effect on HCEC-1CT was more limited. Application of rhodamine-labelled PA demonstrated that the fatty acid is incorporated into the plasma membrane of HCT116, which could not be observed in the non-tumorigenic cell line. Down-streaming into the intracellular compartment, a pronounced rearrangement of actin cytoskeleton was evident in both cell lines (OA and PA; 25 and 100 µM). This was accompanied by a variation of translocation efficiency of the mechanosensitive co-transcription factor YAP1, albeit with a stronger effect seen for PA and the cancer cells. Untargeted proteomic analysis confirmed that exposure to OA and PA could alter the response capacity of HCT116 cells to fluid shear stress. Taken together, OA and PA were able to functionally modulate the mechanosensory apparatus of intestinal cells, implying a novel role for dietary fatty acids in the regulation of intestinal pathophysiology.

Activation of autophagy triggers mitochondrial loss and changes acetylation profile relevant for mechanotransduction in bladder cancer cells - Maximilian Jobst; Endre Kiss; Christopher Gerner; Doris Marko; Giorgia Del Favero (Archives of Toxicology, 2023)
Bladder cells are constantly exposed to multiple xenobiotics and bioactive metabolites. In addition to this challenging chemical environment, they are also exposed to shear stress originating from urine and interstitial fluids. Hence, physiological function of bladder cells relies on a high biochemical and biomechanical adaptive competence, which, in turn, is largely supported via autophagy-related mechanisms. As a negative side of this plasticity, bladder cancer cells are known to adapt readily to chemotherapeutic programs. At the molecular level, autophagy was described to support resistance against pharmacological treatments and to contribute to the maintenance of cell structure and metabolic competence. In this study, we enhanced autophagy with rapamycin (1–100 nM) and assessed its effects on the motility of bladder cells, as well as the capability to respond to shear stress. We observed that rapamycin reduced cell migration and the mechanical-induced translocation potential of Krüppel-like transcription factor 2 (KLF2). These effects were accompanied by a rearrangement of cytoskeletal elements and mitochondrial loss. In parallel, intracellular acetylation levels were decreased. Mechanistically, inhibition of the NAD + -dependent deacetylase sirtuin-1 (SIRT1) with nicotinamide (NAM; 0.1–5 mM) restored acetylation levels hampered by rapamycin and cell motility. Taken together, we described the effects of rapamycin on cytoskeletal elements crucial for mechanotransduction and the dependency of these changes on the mitochondrial turnover caused by autophagy activation. Additionally, we could show that targeted metabolic intervention could revert the outcome of autophagy activation, reinforcing the idea that bladder cells can easily adapt to multiple xenobiotics and circumvent in this way the effects of single chemicals.

Metabolic phenotyping of tear fluid as a prognostic tool for personalised medicine exemplified by T2DM patients - Julia Brunmair; Andrea Bileck; Doreen Schmidl; Gerhard Hagn; Samuel M. Meier-Menches; Nikolaus Hommer; Andreas Schlatter; Christopher Gerner; Gerhard Garhöfer (EPMA Journal, 2022)
Background/aims Concerning healthcare approaches, a paradigm change from reactive medicine to predictive approaches, targeted prevention, and personalisation of medical services is highly desirable. This raises demand for biomarker signatures that support the prediction and diagnosis of diseases, as well as monitoring strategies regarding therapeutic efficacy and supporting individualised treatments. New methodological developments should preferably rely on non-invasively sampled biofluids like sweat and tears in order to provide optimal compliance, reduce costs, and ensure availability of the biomaterial. Here, we have thus investigated the metabolic composition of human tears in comparison to finger sweat in order to find biofluid-specific marker molecules derived from distinct secretory glands. The comprehensive investigation of numerous biofluids may lead to the identification of novel biomarker signatures. Moreover, tear fluid analysis may not only provide insight into eye pathologies but may also be relevant for the prediction and monitoring of disease progression and/ or treatment of systemic disorders such as type 2 diabetes mellitus. Methods Sweat and tear fluid were sampled from 20 healthy volunteers using filter paper and commercially available Schirmer strips, respectively. Finger sweat analysis has already been successfully established in our laboratory. In this study, we set up and evaluated methods for tear fluid extraction and analysis using high-resolution mass spectrometry hyphenated with liquid chromatography, using optimised gradients each for metabolites and eicosanoids. Sweat and tears were systematically compared using statistical analysis. As second approach, we performed a clinical pilot study with 8 diabetic patients and compared them to 19 healthy subjects. Results Tear fluid was found to be a rich source for metabolic phenotyping. Remarkably, several molecules previously identified by us in sweat were found significantly enriched in tear fluid, including creatine or taurine. Furthermore, other metabolites such as kahweol and various eicosanoids were exclusively detectable in tears, demonstrating the orthogonal power for biofluid analysis in order to gain information on individual health states. The clinical pilot study revealed that many endogenous metabolites that have previously been linked to type 2 diabetes such as carnitine, tyrosine, uric acid, and valine were indeed found significantly up-regulated in tears of diabetic patients. Nicotinic acid and taurine were elevated in the diabetic cohort as well and may represent new biomarkers for diabetes specifically identified in tear fluid. Additionally, systemic medications, like metformin, bisoprolol, and gabapentin, were readily detectable in tears of patients. Conclusions The high number of identified marker molecules found in tear fluid apparently supports disease development prediction, developing preventive approaches as well as tailoring individual patients’ treatments and monitoring treatment efficacy. Tear fluid analysis may also support pharmacokinetic studies and patient compliance control.

Metabo-tip: a metabolomics platform for lifestyle monitoring supporting the development of novel strategies in predictive, preventive and personalised medicine - Julia Brunmair; Andrea Bileck; Thomas Stimpfl; Florian Raible; Giorgia Del Favero; Samuel M. Meier-Menches; Christopher Gerner (EPMA Journal, 2021)
Background/aims Exposure to bioactive compounds from nutrition, pharmaceuticals, environmental contaminants or other lifestyle habits may affect the human organism. To gain insight into the effects of these influences, as well as the fundamental biochemical mechanisms behind them, individual molecular profiling seems to be a promising tool and may support the further development of predictive, preventive and personalised medicine. Methods We developed an assay, called metabo-tip for the analysis of sweat, collected from fingertips, using mass spectrometry—by far the most comprehensive and sensitive method for such analyses. To evaluate this assay, we exposed volunteers to various xenobiotics using standardised protocols and investigated their metabolic response. Results As early as 15 min after the consumption of a cup of coffee, 50 g of dark chocolate or a serving of citrus fruits, significant changes in the sweat composition of the fingertips were observed, providing relevant information in regard to the ingested substances. This included not only health-promoting bioactive compounds but also potential hazardous substances. Furthermore, the identification of metabolites from orally ingested medications such as metamizole indicated the applicability of this assay to observe specific enzymatic processes in a personalised fashion. Remarkably, we found that the sweat composition fluctuated in a diurnal rhythm, supporting the hypothesis that the composition of sweat can be influenced by endogenous metabolic activities. This was further corroborated by the finding that histamine was significantly increased in the metabo-tip assay in individuals with allergic reactions. Conclusion Metabo-tip analysis may have a large number of practical applications due to its analytical power, non-invasive character and the potential of frequent sampling, especially regarding the individualised monitoring of specific lifestyle and influencing factors. The extraordinarily rich individualised metabolomics data provided by metabo-tip offer direct access to individual metabolic activities and will thus support predictive preventive personalised medicine.

Exploring the dermotoxicity of the mycotoxin deoxynivalenol: combined morphologic and proteomic profiling of human epidermal cells reveals alteration of lipid biosynthesis machinery and membrane structural integrity relevant for skin barrier function - Giorgia Del Favero; Lukas Janker; Benjamin Neuditschko; Julia Hohenbichler; Endre Kiss; Lydia Woelflingseder; Christopher Gerner; Doris Marko (Archives of Toxicology, 2021)
Deoxynivalenol (vomitoxin, DON) is a secondary metabolite produced by Fusarium spp . fungi and it is one of the most prevalent mycotoxins worldwide. Crop infestation results not only in food and feed contamination, but also in direct dermal exposure, especially during harvest and food processing. To investigate the potential dermotoxicity of DON, epidermoid squamous cell carcinoma cells A431 were compared to primary human neonatal keratinocytes (HEKn) cells via proteome/phosphoproteome profiling. In A431 cells, 10 µM DON significantly down-regulated ribosomal proteins, as well as mitochondrial respiratory chain elements (OXPHOS regulation) and transport proteins (TOMM22; TOMM40; TOMM70A). Mitochondrial impairment was reflected in altered metabolic competence, apparently combined with interference of the lipid biosynthesis machinery. Functional effects on the cell membrane were confirmed by live cell imaging and membrane fluidity assays (0.1–10 µM DON). Moreover, a common denominator for both A431 and HEKn cells was a significant downregulation of the squalene synthase (FDFT1). In sum, proteome alterations could be traced back to the transcription factor Klf4, a crucial regulator of skin barrier function. Overall, these results describe decisive molecular events sustaining the capability of DON to impair skin barrier function. Proteome data generated in the study are fully accessible via ProteomeXchange with the accession numbers PXD011474 and PXD013613.

Cancer-associated fibroblast-derived WNT2 increases tumor angiogenesis in colon cancer - Daniela Unterleuthner; Patrick Neuhold; Katharina Schwarz; Lukas Janker; Benjamin Neuditschko; Harini Nivarthi; Ilija Crncec; Nina Kramer; Christine Unger; Markus Hengstschläger; Robert Eferl; Richard Moriggl; et al. (Angiogenesis, 2020)
WNT2 acts as a pro-angiogenic factor in placental vascularization and increases angiogenesis in liver sinusoidal endothelial cells (ECs) and other ECs. Increased WNT2 expression is detectable in many carcinomas and participates in tumor progression. In human colorectal cancer (CRC), WNT2 is selectively elevated in cancer-associated fibroblasts (CAFs), leading to increased invasion and metastasis. However, if there is a role for WNT2 in colon cancer, angiogenesis was not addressed so far. We demonstrate that WNT2 enhances EC migration/invasion, while it induces canonical WNT signaling in a small subset of cells. Knockdown of WNT2 in CAFs significantly reduced angiogenesis in a physiologically relevant assay, which allows precise assessment of key angiogenic properties. In line with these results, expression of WNT2 in otherwise WNT2-devoid skin fibroblasts led to increased angiogenesis. In CRC xenografts, WNT2 overexpression resulted in enhanced vessel density and tumor volume. Moreover, WNT2 expression correlates with vessel markers in human CRC. Secretome profiling of CAFs by mass spectrometry and cytokine arrays revealed that proteins associated with pro-angiogenic functions are elevated by WNT2. These included extracellular matrix molecules, ANG-2, IL-6, G-CSF, and PGF. The latter three increased angiogenesis. Thus, stromal-derived WNT2 elevates angiogenesis in CRC by shifting the balance towards pro-angiogenic signals.

Impact of a synthetic cannabinoid (CP-47,497-C8) on protein expression in human cells: evidence for induction of inflammation and DNA damage - Andrea Bileck; Franziska Ferk; Halh Al-Serori; Verena J. Koller; Besnik Muqaku; Alexander Haslberger; Volker Auwärter; Christopher Gerner; Siegfried Knasmüller (Archives of Toxicology, 2016)

Increased protein synthesis by cells exposed to a 1,800-MHz radio-frequency mobile phone electromagnetic field, detected by proteome profiling - Christopher Gerner; Verena Haudek; Ulla Schandl; Editha Bayer; Nina Gundacker; Hans Peter Hutter; Wilhelm Mosgoeller (International Archives of Occupational and Environmental Health, 2010)

Reduced stress tolerance of glutamine-deprived human monocytic cells is associated with selective down-regulation of Hsp70 by decreased mRNA stability - Maja Munk Eliasen; Marianne Brabec; Christopher Gerner; Jürgen Pollheimer; Herbert Auer; Maria Zellner; Gertrude Weingartmann; Fritz Garo; Erich Roth; Rudolf Oehler (Journal of Molecular Medicine, 2006)